2018
DOI: 10.5812/ijpbs.61329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Childhood Attention-Deficit/Hyperactivity Disorder (ADHD) in Methamphetamine Dependence: A Descriptive Study

Abstract: Background: The high comorbidity of psychiatric disorders and substance dependence has been reported in children clinical and epidemiological as a study. Objectives: The aim of this study was to determine the prevalence of childhood attention-deficit/hyperactivity disorder (ADHD) among methamphetamine dependence. Methods: This study was a descriptive cross -sectional study that has been done in 2015 -2016. The study population consisted of individuals referred with methamphetamine dependence to Kermanshah Fara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This difference may account for some of our observations. For example, a study found a 30% prevalence of childhood attention-deficit/hyperactivity disorder in methamphetamine users, 45 which might indicate that a subpopulation with more hyperactivity traits such as restlessness could have yielded more conclusive results in the present study, as well as for other outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…This difference may account for some of our observations. For example, a study found a 30% prevalence of childhood attention-deficit/hyperactivity disorder in methamphetamine users, 45 which might indicate that a subpopulation with more hyperactivity traits such as restlessness could have yielded more conclusive results in the present study, as well as for other outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…This could result in people being treated for ADHD being included in the study cohort. To minimise ascertainment bias, we excluded individuals diagnosed with or being treated for ADHD, but because of strong links between ADHD, mental health issues and substance use,65 66 we will conduct a sensitivity analysis to determine whether this exclusion significantly impacts our findings. A second limitation is that only people interacting with the health system following methamphetamine use will be included in the study.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Methamphetamine increases the body metabolism and creates a state of vitality, increases consciousness and gives the user a sense of increased energy. 3 It is highly addictive and causes more damage to the person than other amphetamines. 3,4 The evidence shows that experiencing negative emotions and avoiding negative emotional states as well as distress tolerance are related to incompatibility, 5 antisocial behaviors, 6 anxiety issues, 7 and tendency to abuse alcohol and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is highly addictive and causes more damage to the person than other amphetamines. 3,4 The evidence shows that experiencing negative emotions and avoiding negative emotional states as well as distress tolerance are related to incompatibility, 5 antisocial behaviors, 6 anxiety issues, 7 and tendency to abuse alcohol and drugs. [8][9][10] Distress tolerance is defined as the individual's capability to experience and tolerate negative emotional states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation